CRITICAL CURRENT, MAGNETIC IRREVERSIBILITY LINE AND RELAXATION IN A SINGLE TL-O-LAYER-1223 SUPERCONDUCTOR - Zheng, D; Campbell, A; Liu, R; Edwards, P (1993)
We have carried out systematic studies on the critical current, magnetic irreversibility line and magnetic relaxation for a c-axis orientated powdered (Tl0.5Pb0.5)Sr2Ca2Cu3O9 (Tl-1223) sample. This single TlO layer compound, in comparison with the double TlO layer compound Tl2Ba2Ca2Cu3O10 (Tl-2223), exhibited a high irreversibility line, less temperature and magnetic field dependent critical currents and a smaller flux creep rate. The substantially greater flux pinning ability of Tl-1223 can be understood in terms of its structural characteristics; in Tl-1223, there is only one insulating TlO layer between superconducting CuO2 blocks while there are two in Tl-2223. The increase in the number (and distance) of insulating layers weakens the Josephson coupling between CuO2 blocks along the c-axis and the results in a decrease in the value of Jc. This decoupling between blocks causes the vortex lattice to break into pancake-like vortices which are easily thermally activated. © 1993.